THERMAL AND HYDROLOGICAL CONDITIONS OF REPTILE SPECIES-AT-RISK HABITAT ALONG EASTERN GEORGIAN BAY DURING CRITICAL LIFE STAGES - Smolarz, Alanna (My University, 2017)
Reptiles are the vertebrate taxon with the highest percentage of at-risk species in Canada, many of which exist at the northern limit of their species’ home range in Ontario. Numerous reptiles are found in the Georgian Bay area; however, factors limiting their distribution in Ontario are poorly understood. It is likely that the thermal and hydrological conditions of a reptile’s critical habitat are contributing factors. Specifically, peatlands serve as ideal hibernacula for the threatened Eastern Massasauga Rattlesnake (Sistrurus catenatus) while moss cushions may provide freshwater turtles, including the threatened Blanding’s Turtle (Emydoidea blandingii) and endangered Spotted Turtle (Clemmys guttata), with nesting opportunities on open rock barrens. Although different in their functional purpose at opposite life stages for two separate orders of reptiles, these ecosystems provide suitable conditions to meet the physiological needs of the reptiles utilizing them. This analysis characterizes the thermal and hydrological conditions of moss-dominated ecosystems from a reptile species-at-risk perspective. The interaction between the water table and the frost line is important when assessing the winter survival of Eastern Massasauga Rattlesnakes hibernating in peatland hummocks. Larger hummocks are more ideal as they have a lower chance of becoming flooded in the winter while still providing protection from the advancing frost line. Ideally, hummocks that are 30-35 cm tall provide the greatest chance of survival when snakes hibernate 20-25 cm below the surface. Subsurface temperatures in relation to snow depth, as it is influenced by tree stand characteristics, was also assessed. This resulted in the conclusion that the presence, absence, timing, and frequency of freeze and thaw events is likely more important than snow depth when it comes to winter survival. Similar to rattlesnake hibernacula, turtle nests can be inundated for extended periods of time or exposed to extreme temperatures which reduces their chance of survival. The water storage dynamics of 22 hillslope and 12 hilltop moss cushions along with the temperature dynamics at nine locations were characterized. Although it was determined hilltop locations had greater water storage capabilities, continuously monitored moss cushions responded very quickly to rainfall events whereby sites were inundated for less than 12 hours. Average subsurface temperatures decreased with depth as did temperature fluctuations, both of which were positively correlated but not significantly affected by canopy openness. However, due to their tendency to grow on flat surfaces, not all moss cushions are suitable nesting sites. Moreover, temperatures that ensure proper development and equal ratios of male-to-female turtles were not achieved suggesting that this is a potential factor limiting the northern distribution of turtles in Ontario. In order to properly asses the vulnerability of these populations to threats including habitat loss and climate change, the habitat requirements of different species at critical life stages needs to be understood. Therefore, conservationists can use this study to implement mitigation strategies that consider impacts on the thermal and hydrological dynamics within reptile habitat.
Keywords: Reptiles; Species at Risk; Habitat; Peatlands; Moss; Snake Hibernation; Turtle Nesting; Georgian Bay